2019
DOI: 10.3389/fendo.2019.00463
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Types of Exercise Training on the Cortisol Awakening Response in Children

Abstract: Context: Due to great variability of the hypothalamus-pituitary-adrenal (HPA)-axis, research has to produce better-controlled findings to make a more meaningful statement regarding the effect of exercise training (ET) on the cortisol awakening response (CAR), especially in children. Objective: The aim of the study was to investigate the effects of different ET interventions on the CAR in children. Design and setting: We conducted a short-term training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The participant self-reports denoted decreased stress level for the THR phase and would support the CARi decrease being associated with lesser stress. Another study found that children who participated in cardiovascular exercise displayed increased CARi, whereas children in the motor exercise group displayed decreased CARi (Wegner et al, 2019 ). A meta-analysis found lower basal cortisol to be associated with increased physical activity or physical fitness (Mücke et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The participant self-reports denoted decreased stress level for the THR phase and would support the CARi decrease being associated with lesser stress. Another study found that children who participated in cardiovascular exercise displayed increased CARi, whereas children in the motor exercise group displayed decreased CARi (Wegner et al, 2019 ). A meta-analysis found lower basal cortisol to be associated with increased physical activity or physical fitness (Mücke et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…We used AUCg to index total T secretion on each of the three individual days across monthslong collection periods that are uniform across participants (Pruessner et al., 2003). This strategy appears in recent endocrine literature (e.g., Wegner et al., 2019), but the precision of our results is constrained by the number of collection periods. Thus, readers are encouraged to interpret the results in this paper as awaiting replication.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary cortisol was chosen as a parameter to determine stress levels because CAR is a reliable measure of the acute responsiveness of the hypothalamic-pituitary-adrenal (HPA) axis and can serve as a useful index of adrenocortical activity [21]. Furthermore, a literature review previously explained that the HPA axis is a highly stress-responsive system and shows a strong diurnal pattern with the glucocorticoid cortisol as an end product [22]. Several protocols had been obeyed in measuring CAR in salivary cortisol.…”
Section: Discussionmentioning
confidence: 99%